2016
DOI: 10.1155/2016/5713962
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Curing Light through Moist, Air-Dried, and EDTA Treated Dentine and Enamel

Abstract: Objective. This study measured light transmission through enamel and dentin and the effect of exposed dentinal tubules to light propagation. Methods. Light attenuation through enamel and dentin layers of various thicknesses (1 mm, 2 mm, 3 mm, and 4 mm) was measured using specimens that were (1) moist and (2) air-dried (n = 5). Measurements were repeated after the specimens were treated with EDTA. Specimens were transilluminated with a light curing unit (maximum power output 1869 mW/cm2), and the mean irradianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…This result is in corroborates with the finding of Rueggeberg et al (8) . It was obvious that, high intensity group with 1mm tooth structure thickness reported highest depth of cure as compared to the other group due to decreasing the distance between the light curing tip and resin composite restoration so reduce the amount of light scattering and energy attenuation when the light passes through enamel and dentin producing so could guarantee adequate depth of cure (15) . Also, this was in agreement with (17) whom stated that, the resin composite has the property of dispersing the light of the light curing unit, so when the light passes through the bulk of the resin composite, light intensity is attenuated due to the light being scattered by filler particles and the resin matrix.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This result is in corroborates with the finding of Rueggeberg et al (8) . It was obvious that, high intensity group with 1mm tooth structure thickness reported highest depth of cure as compared to the other group due to decreasing the distance between the light curing tip and resin composite restoration so reduce the amount of light scattering and energy attenuation when the light passes through enamel and dentin producing so could guarantee adequate depth of cure (15) . Also, this was in agreement with (17) whom stated that, the resin composite has the property of dispersing the light of the light curing unit, so when the light passes through the bulk of the resin composite, light intensity is attenuated due to the light being scattered by filler particles and the resin matrix.…”
Section: Discussionmentioning
confidence: 98%
“…light transmission is considerably influenced when there is dentin or enamel between the light source and a light irradiance power detector. This issue has relevance when light curing adhesives and resin composites are cured through dentin and enamel (15) . Therefore, two different tooth structure plate thickness were prepared in class III cavities to assess the effect of thickness of enamel and dentin on the degree of curing of resin composite restoration with different two light intensities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of Oesterle and Shellhart [9] showed that transillumination through extracted maxillary incisors resulted in sufficiently high bond strengths of brackets, particularly when the curing time was 50 s. From the clinical point of view, the optimal bond strength has been considered to be at least 5.9 MPa [11], whereas the risk for enamel fractures increases when the bond strength is higher than 9.7 MPa [12]. Heravi et al [10] on the other hand, found that light curing through premolars resulted in bond strengths below clinically acceptable values even if curing time was increased to 80 s. In a previous study we studied the light propagation through the dental hard tissues and showed that light penetrates enamel better than dentin, and that penetration of light is enhanced if enamel and dentin are moisturized [6].…”
Section: Introductionmentioning
confidence: 97%
“…However, convexity of the labial tooth surface and the bracket material hinder or obstruct direct light propagation resulting in incomplete polymerization of the adhesive at the center of the bracket. We have shown previously that polymerization of the adhesive under a metal bracket can be enhanced by adding light transmitting glass fibers in the resin interface [5,6].…”
Section: Introductionmentioning
confidence: 99%